2016
DOI: 10.5414/cn108940
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery calcification in CKD-5D 
patients is tied to adverse cardiac function 
and increased mortality

Abstract: Background: Coronary artery calcification (CAC) is common in patients with chronic kidney disease on hemodialysis (CKD-5D) and is an important predictor of mortality. However, cardiac functional links between CAC and mortality have not been well established. This study tested the hypothesis that CAC increases mortality by adversely affecting cardiac function. Methods: Patients were recruited from 37 regional dialysis centers. 2-D and Doppler echocardiographic analyses were performed, and CAC was measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 48 publications
(52 reference statements)
0
14
2
1
Order By: Relevance
“…23 Elevated calcium and phosphorus levels are associated with greater coronary artery calcification, which is strongly related to increased mortality and excess cardiovascular events. [24][25][26][27][28] Additionally, although Tentori et al 21 observed no effect modification of the PTH-mortality association by black/African American race, we show that a greater proportion of US black/African American (vs non-black/African American) patients are included in the highest risk category (PTH > 600 pg/mL) despite greater cinacalcet and active vitamin D use.…”
Section: Discussioncontrasting
confidence: 59%
“…23 Elevated calcium and phosphorus levels are associated with greater coronary artery calcification, which is strongly related to increased mortality and excess cardiovascular events. [24][25][26][27][28] Additionally, although Tentori et al 21 observed no effect modification of the PTH-mortality association by black/African American race, we show that a greater proportion of US black/African American (vs non-black/African American) patients are included in the highest risk category (PTH > 600 pg/mL) despite greater cinacalcet and active vitamin D use.…”
Section: Discussioncontrasting
confidence: 59%
“…Patients with ESRD were recruited from within an ongoing study at our institution 13 . Demographics for patients with ESRD (n = 29) and healthy controls (n = 33) are detailed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Statistics show that the mortality rate of patients with chronic kidney disease (CKD) is significantly higher than the general population, especially among ­dialysis patients, and cardiovascular disease is the l­eading cause of death [12]. SHPT is a common ­complication observed in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%